Anti-acne activity and nanoemulsion formulation of a combination of lime peel (Citrus aurantifolia (Christm.) Swingle) extract and essential oil - Muhammad Aqsyal; Yesi Desmiaty; Siti Umrah Noor (Faculty of Pharmacy, Universitas Pancasila, 2026)
Acne is a common skin disorder closely associated with bacterial infection, particularly Cutibacterium acnes and Staphylococcus epidermidis. Lime peel contains flavonoids, saponins, phenolics, tannins, and essential oils that exhibit antibacterial potential. This study aims to evaluate the anti-acne activity of a combination of lime peel extract and essential oil and to formulate it into a nanoemulsion dosage form. An experimental study was conducted using the disk diffusion method to assess anti-acne activity. The inhibition zone was measured after 24-hour incubation at 37 °C. Nanoemulsions were then prepared through ultrasonic processing and characterised using PSA and TEM. The results demonstrated that the extract–essential oil combinations at ratios 1:1, 1:2, and 2:1 produced greater inhibition zones than the single agents, indicating a synergistic effect. The nanoemulsion formulated with Alkamuls CRH 40, glycerin, and VCO produced particles <100 nm with a polydispersity index of 0.072–0.141, although the zeta potential values (−14.1 to −16.7 mV) indicated suboptimal stability. Overall, the combination of lime peel extract and essential oil exhibited significant anti-acne activity and has the potential to be developed as a topical nanoemulsion-based preparation.